On the Car-Following Theory - Usenik, Janez; Batista, Milan (Promet - Traffic&Transportation, 2012)
The article deals with bumper-to-bumper driving. A .systemicapproach to car-following (bumper-to-bumper driving)i.s described and the mathematical model has been developedand solved. With this approach an algorithm for analytical andnumerical solutions has been developed.